Development of Google Sites-Based E-Learning Animation Video for Learning Atomic Theory - Putri, Rizka Amalia; Rahayu, Rosika; Nurlaili, Nurlaili; Lestari, Sri; Rahmadani, Agung (FKIP - Universitas Riau, 2025)
The rapid advancement of digital technology offers significant opportunities to develop innovative, interactive, and adaptive learning media that align with the learning characteristics of the 21st-century generation. This study aims to develop and evaluate animated video-based instructional materials on the topic of atomic theory development, integrated through Google Sites, and to determine their validity, practicality, and effectiveness. The research employed the Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The study involved two subject matter experts, two media experts, two instructional practitioners, and tenth-grade students from SMAIT Istiqamah YPAIT Balikpapan. The validation results indicated a high level of feasibility with a score of 94.92% (very valid). Practicality assessments yielded scores of 90.73% from teachers (very practical) and 76.74% from students (practical). The effectiveness test demonstrated improved learning outcomes, with an N-Gain score of 0.70 (medium category) and an effect size of 3.71 (very strong category). These findings suggest that Google Sites-based animated video media effectively enhance students’ conceptual understanding, motivation, and learning independence, making it a relevant and innovative alternative for digital-based chemistry learning.